Islamic Bioethics, Porcine Therapeutics and Porcine Xenotransplantation: Islamic Perspectives - Kee Lam Wong; Waleed Fekry Faris (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Medical personnel (Healthcare Providers, HCPs) have the moral and ethical obligations of fulfilling the health needs of the patients and must be attentive to the patients’ cultural and religious needs. In Hong Kong, we have a small but significant Muslim population but very few Muslim HCPs. More often than not, we simply neglect or forget about the needs for our Muslim patients. The main cause is our lack of knowledge about Islamic Bioethics (IBE) especially on what treatments and procedures are permitted or prohibited. This article provides a detailed analysis to enable HCPs to understand and make decisions on permitted treatments for Muslim patients. This is extremely important for non-Muslim HCPs who have only mediocre or no knowledge in Islam. This study is a comprehensive review on the application of IBE, from their development since the contemporary period to Modern Times, the contributions of Islamic laws and the frames of belief in Sickness and Treatment. A special emphasis is provided for the mechanisms of relieves in reversing Prohibition. Pork is prohibited in Islam. The authors choose Porcine Therapeutics and Porcine Xenotransplantation (PXT) as the model to illustrate how Prohibition is determined in medical therapeutics and how the Prohibition can be reversed such that appropriate treatments can be offered and accepted. This model has the potential of application to all forms of therapeutics and may facilitate the interactions and decision making among HCPs and Muslim Patients. The principles of Shari’ah and maqāṣid shari‘ah, the basis of IBE in relation to sickness and treatment, and their applications to general biomedical issues, Porcine Therapeutics and PXT are explained in details. The prohibitions on the latter two areas can be reversed by invoking Transformation (istihalah), Dire Necessity (ḍarūrah), or Public Interest (maṣlahāh). The current permissibility in Xenotransplantation (XT) is considered to be premature and Dire Necessity (ḍarūrah) cannot be invoked because benefits from XT and PXT have not been established. Public Interest (maṣlahāh) can be invoked to allow for Experimental Research and Clinical Studies in PXT.